2022
DOI: 10.18240/ijo.2022.09.19
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection with keratitis as the first clinical manifestation

Abstract: AIM: To report a case which keratitis is the first clinical manifestation of COVID-19 that occurred 3d earlier than the common COVID-19 symptoms. METHODS: Regular slit lamp examination, corneal scraping test, and chest computed tomography (CT) were performed for patients with COVID-19 infection. The ophthalmologic treatment included ganciclovir eye drop (50 mg/mL, 6 times/d). The treatment for diarrhea included Guifu Lizhong pills (TID). The antiviral therapy consisted of oseltamivir (75 mg capsule Q12H); ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, our patients did not respond to antiviral and steroid eye drops, demonstrating a loose link to viral infection. In most cases, infectious keratitis occurs monocularly [19][20][21] . Nevertheless, five of 40 patients developed bilateral keratitis in our study.…”
Section: Resultsmentioning
confidence: 99%
“…However, our patients did not respond to antiviral and steroid eye drops, demonstrating a loose link to viral infection. In most cases, infectious keratitis occurs monocularly [19][20][21] . Nevertheless, five of 40 patients developed bilateral keratitis in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several studies providing evidence on the impact of COVID-19 on the eye [1][2][3][4][5][6][7][8][9][10][11][12][25][26][27][28] , few of them focus on its impact on visual perception [13][14][15] . The present study has shown that there appears to be an impairment of color and achromatic-chromatic contrast vision in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…He wore an N95 mask but did not wear anything to protect his eyes, suggesting that 2019-nCoV transmission through the ocular surface must not be ignored [11] . In a case report, a new type of atypical keratitis is a clinical manifestation of COVID-19, which could appear 3d earlier than common symptoms of COVID-19 [12] . It is indicated that the cornea and conjunctiva are one of the transmission routes of COVID-19.…”
Section: Introductionmentioning
confidence: 93%